Initial presentation of early rheumatoid arthritis. - Lauri Weman; Henri Salo; Laura Kuusalo; Johanna Huhtakangas; Johanna Kärki; Paula Vähäsalo; Maria Backström; Tuulikki Sokka-Isler (PLoS ONE)
Objectives To study the joint distribution and clinical picture of rheumatoid arthritis (RA) at the initial presentation in seropositive (anti-citrullinated protein antibody (ACPA) and/or rheumatoid factor (RF) positive) and negative patients and the effect of duration of symptoms on the clinical picture. Methods Data of patients who received reimbursement for DMARDs for newly diagnosed RA in 1/2019 to 9/2021 were extracted from the national databases. Joint counts, presence of symmetrical swelling, other disease activity measures, and patient reported outcomes (PROs) were compared in seropositive and negative patients. Regression analyses were applied to compare clinical variables in patients with duration of symptoms of <3, 3-6, and >6 months, adjusted for age, sex, and seropositivity. Results Data of 1816 ACPA and RF-tested patients were included. Symmetrical swelling was present in 75% of patients. Seronegative versus positive patients had higher value for all disease activity measures and PROs including median swollen joint count (SJC46 10 versus 5) and DAS28 (4.7 versus 3.7), (p<0.001). Patients diagnosed in <3 months had higher median pain VAS (62 versus 52 and 50, p<0.001) and HAQ (1.1 versus 0.9 and 0.75, p = 0.002) compared to those with a duration of symptoms of 3-6 and >6 months. Patients diagnosed >6 months were ACPA-positive more frequently (77% versus 70% in other groups, p = 0.045). Conclusion Incident RA presents mainly as symmetric arthritis. Seronegative patients have higher disease burden at the initial presentation. Patients experiencing more severe pain and decreased functional ability are diagnosed earlier, regardless of ACPA- status.